2003
DOI: 10.1007/s00438-002-0782-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mapping of Brassica oleracea based on ESTs from Arabidopsis thaliana: complexity of the comparative map

Abstract: Expressed sequence tags (ESTs) from the Arabidopsis thaliana sequencing project were used to construct a genetic RFLP map for Brassica oleracea. Of the 110 A. thaliana ESTs tested, 95 were found to be informative RFLP probes in map construction. In total, 212 new loci corresponding to the 95 ESTs were added to the existing genetic map of B. oleracea. The enriched map covers all nine basic linkage groups and confirms that the chromosomes of B. oleracea and A. thaliana are similar in linear organization. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 46 publications
0
28
0
1
Order By: Relevance
“…It is worth noting that we could expect any remnants of the fusions only in the case of chromosomes 1, 2 and 5, where the ancient pericentromeric regions had been taken apart: in fusions that resulted in the formation of present chromosomes 3 and 4 only telomeric sequences could be expected. We also found that it is impossible to detect remnants of more ancient chromosomal rearrangements at the level of indel distribution, though they can be easily detected by bioinformatic (23,56,57) and hybridization approaches (58,59), where coding sequences are mainly involved.…”
Section: Discussionmentioning
confidence: 92%
“…It is worth noting that we could expect any remnants of the fusions only in the case of chromosomes 1, 2 and 5, where the ancient pericentromeric regions had been taken apart: in fusions that resulted in the formation of present chromosomes 3 and 4 only telomeric sequences could be expected. We also found that it is impossible to detect remnants of more ancient chromosomal rearrangements at the level of indel distribution, though they can be easily detected by bioinformatic (23,56,57) and hybridization approaches (58,59), where coding sequences are mainly involved.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Brassica and Arabidopsis diverged from a common ancestor approximately 14–20 million years ago (Yang et al, 1999), and the genome of Brassica species underwent polyploidization, accompanied by gene deletion and rearrangements (Cavell et al, 1998; Lagercrantz, 1998; Ryder et al, 2001; Babula et al, 2003; Lukens et al, 2003). Therefore, many comparative mapping studies have unraveled the extensive genome homology and microsynteny between the A, B, and C genomes of Brassica species and between Brassica species and A. thaliana (Parkin et al, 2005; Jiang et al, 2011; Wang et al, 2011; Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The homeologous IDBs in different chromosomes would enhance the chance of homeologous reciprocal or nonreciprocal translocations which were already found in several Canadian and Australian cultivars of B. napus where IDBs exchanged between A7 and C6 [53,54]. Lyask et al [25] found that the most frequent chromosome rearrangements involving the At4-b contig are inversions, whilst comparative mapping has indicated that 43% of Brassica genomicregions with homeology to Arabidopsis chromosomes involved inversions [35]. It has been suggested that rearrangements such as translocations or inversions might reduce or prevent undesirable pairing and recombination between homeologous chromosomes/chromosome regions and lead to reproductive isolation between populations, and eventually contribute to the speciation processes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more detailed evidence for the ancestral segmental chromosomal duplications leading to effective triplication in Brassica diploids has been obtained from partial genome sequencing and comparative chromosome painting [22,25,32-34]. However, comparative sequence analysis indicates that various mechanisms of genome evolution have contributed to many situations where either more or less than three paralogous genes, corresponding to single orthologues in Arabidopsis , are present in the Brassica A or C genome [26,28,35-37]. …”
Section: Introductionmentioning
confidence: 99%